Pure desire eaudiobook How one man's triumph can help others break free from sexual temptation. - Roberts, Ted (Tantor Media, 2020)
Hope and Healing to Break Free From Sexual Addiction There is a battle going on. Millions of victims are trapped in the struggle of sexual addiction with no apparent way out. Pure Desire is the answer to this desperate cry for help from men and women who have tried to build sexual holiness into their lives and failed . . . and failed . . . and failed. This book is also for the shattered souls of mates who are puzzled, shamed, and wounded by their husband's or wife's sexual bondage and secret life. And, this book is for the Church to come alongside those who have come to them for help. Here is hope for establishing healthy personal boundaries with proven, practical applications to claim Christ's healing power and presence, perhaps for the first time. If you, someone you love, or someone you are counseling struggles with sexual addiction, Pure Desire is an anchor amid rough waters and the offer of a new appreciation for Christ's healing power and presence. The time is now to begin walking in victory and help others to do the same. Learn how to tackle this issue with confidence, clarity, and biblical perspective.